Virulence adaptations of Pseudomonas aeruginosa isolated from patients with non-cystic fibrosis bronchiectasis - Woo, Taylor E. (Microbiology (Reading), 2016)
Pseudomonas aeruginosa is a major pathogen in chronic lung diseases such as cystic fibrosis (CF) and non-cystic fibrosis bronchiectasis (nCFB). Much of our understanding regarding infections in nCFB patients is extrapolated from findings in CF with little direct investigation on the adaptation of P. aeruginosa in nCFB patients. As such, we investigated whether the adaptation of P. aeruginosa was indeed similar between nCFB and CF. From our prospectively collected biobank, we identified 40 nCFB patients who had repeated P. aeruginosa isolates separated by ≥6 months and compared these to a control population of 28 CF patients. A total of 84 nCFB isolates [40 early (defined as the earliest isolate in the biobank) and 41 late (defined as the last available isolate in the biobank)] were compared to 83 CF isolates (39 early and 44 late). We assessed the isolates for protease, lipase and elastase production; mucoid phenotype; swarm and swim motility; biofilm production; and the presence of the lasR mutant phenotype. Overall, we observed phenotypic heterogeneity in both nCFB and CF isolates and found that P. aeruginosa adapted to the nCFB lung environment similarly to the way observed in CF isolates in terms of protease and elastase expression, motility and biofilm formation. However, significant differences between nCFB and CF isolates were observed in lipase expression, which may allude to distinct characteristics found in the lung environment of nCFB patients. We also sought to determine virulence potential over time in nCFB P. aeruginosa isolates and found that virulence decreased over time, similar to CF.